2017
DOI: 10.1590/0034-7167-2017-0114
|View full text |Cite
|
Sign up to set email alerts
|

Older adults abuse in three Brazilian cities

Abstract: Objective: To analyze the police reports fi led by older adults who suffered abuse in order to identify the socio-demographic characteristics of victims and aggressors, type of violence, location, as well as to compare rates in three Brazilian cities in the period from 2009 to 2013. Method: Ecological study, in which 2,612 police reports registered in Police Stations were analyzed. An instrument was used to obtain data from the victim, the aggressor and the type of violence. Results: Psychological abuse predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 18 publications
3
17
0
9
Order By: Relevance
“…As for schooling, data from this survey identified that 40% had completed elementary school, information consistent with a study conducted in Ribeirão Preto, where most of the victims had completed first grade, but most were women. 22 The most prevalent marital status in this sample is that of the married, which is consistent with a survey conducted in Minas Gerais, in which there was a predominance of married elderly victims of violence. 18 However, other literature suggests that marriage may be a positive factor for healthier aging and that the absence of a partner may also be a factor for neglect.…”
Section: Discussionsupporting
confidence: 89%
“…As for schooling, data from this survey identified that 40% had completed elementary school, information consistent with a study conducted in Ribeirão Preto, where most of the victims had completed first grade, but most were women. 22 The most prevalent marital status in this sample is that of the married, which is consistent with a survey conducted in Minas Gerais, in which there was a predominance of married elderly victims of violence. 18 However, other literature suggests that marriage may be a positive factor for healthier aging and that the absence of a partner may also be a factor for neglect.…”
Section: Discussionsupporting
confidence: 89%
“…With regard to the elderly victims of violence, a study carried out in three Brazilian municipalities identified a prevailing age of 60 to 69 years, mostly women and married (22) . Psychological violence predominated in reports of violence, then physical, and in the two municipalities of the Northeast, the financial violence (22) .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the elderly victims of violence, a study carried out in three Brazilian municipalities identified a prevailing age of 60 to 69 years, mostly women and married (22) . Psychological violence predominated in reports of violence, then physical, and in the two municipalities of the Northeast, the financial violence (22) . These findings corroborate with studies on the elderly who attempted suicide (16)(17)(18) and are significant because they identify in low-income populations, where the elderly receive social benefits, there is a greater risk of suffering this kind of violence (22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em relação ao sexo e à cor da pele/etnia das vítimas, a maioria destas eram do sexo feminino e brancas. Dados semelhantes são evidenciados em diversos estudos (Rodrigues, et al, 2017;Garbin, Joaquim, Rovida, & Garbin, 2016;Grilo, & Lombardi Júnior, 2015).…”
Section: Discussionunclassified